Nutritional concerns later in life. Issue 3 (11th August 2021) - Grootswagers, Pol; de Groot, Lisette C. P. G. M.
Abstract : In an ageing society, the preservation of health and function is becoming increasingly important. The present paper acknowledges that ageing is malleable and focuses on diets and key nutritional concerns later in life. It presents evidence for the importance of healthful dietary patterns and points towards specific nutritional concerns later in life and conveys three main messages: (1) considering health maintenance and malnutrition risk, both dietary quality in terms of healthful dietary patterns and dietary quantity are important later in life, (2) ageing-related changes in nutrient physiology and metabolism contribute to the risk of inadequacies or deficiencies for specific nutrients, e.g. vitamin D, vitamin B12 and protein and (3) that current food-based dietary guidelines propagate a shift into the direction of Mediterranean type of diets including more plant-based foods. Limited scientific evidence on nutritional requirements of older adults, along with envisaged shifts towards diets rich in plant foods, are challenges that need to be addressed in order to develop tailored nutritional recommendations and dietary guidance for older adults.